2021
DOI: 10.25259/sni_183_2021
|View full text |Cite
|
Sign up to set email alerts
|

Incidentally discovered dural arteriovenous fistula during middle meningeal artery embolization for the treatment of chronic subdural hematoma

Abstract: Background: The incidence of chronic subdural hematoma (CSDH) is increasing with population age and anticoagulant use. Embolization of the middle meningeal artery (MMA) is an emerging, less invasive alternative to open surgery in treating this condition. Dural arteriovenous fistula (DAVF) is a rare condition whose association with CSDH is not well understood. We present three cases with incidentally discovered DAVFs during MMA embolization for the treatment of CSDH that necessitated adjustments to initial tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Several cases of coexisting CSDH and DAVF have been reported, and these have been described as idiopathic or iatrogenic secondary to burr hole surgery. [10][11][12][13][14][15] Tabibian et al reported that a DAVF was found incidentally in 3 of 30 cases of MMA embolization for CSDH. 15) Currently, no study has indicated that a DAVF can contribute to the formation of CSDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cases of coexisting CSDH and DAVF have been reported, and these have been described as idiopathic or iatrogenic secondary to burr hole surgery. [10][11][12][13][14][15] Tabibian et al reported that a DAVF was found incidentally in 3 of 30 cases of MMA embolization for CSDH. 15) Currently, no study has indicated that a DAVF can contribute to the formation of CSDH.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Tabibian et al reported that a DAVF was found incidentally in 3 of 30 cases of MMA embolization for CSDH. 15) Currently, no study has indicated that a DAVF can contribute to the formation of CSDH.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the MMA may show a potential shunt with the middle meningeal vein, sometimes depicted on selective MMA angiography. 67 ) Some reports have described superior sagittal sinus occlusion through such potential shunts during MMA embolization for CSDH. 68 ) As a result, pressure injection of liquid embolic material should be strictly avoided and meticulous imaging evaluation is mandatory.…”
Section: Procedure-related Complications Of Mma Embolization For Csdhmentioning
confidence: 99%
“…These include venous occlusion or trauma that predispose the existing vascular network to neoangiogenesis and/or inflammatory reactions. [ 8 , 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…ese include venous occlusion or trauma that predispose the existing vascular network to neoangiogenesis and/or inflammatory reactions. [8,14] Here, we present the first reporting of a dAVF following subdural evacuation port system (SEPS) placement for the evacuation of a subdural hematoma (SDH). Patient consent was obtained.…”
Section: Introductionmentioning
confidence: 99%